ISOLASI DAN IDENTIFIKASI BAKTERI ASAM LAKTAT AMILOLITIK DARI INDUSTRI PENGOLAHAN PATI SAGU - Ali, Akhyar; ', Kusumaningrum; ', Yusmarini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Lactic acid bacteria (LAB) that grow on sago starch processing industry is a bacteria that can grow in the sago-based media. Isolates which able to grow on media sago starch has the amylolytic ability and was the potential to be used in modifying the sago starch microbiologically. The purpose of this study was to isolate and identify lactic acid bacteria from sago starch processing industry. Isolation and purification of lactic acid bacteria were carried on MRS agar medium supplemented with 0.2% CaCO3 for subsequent screening of lactic acid bacteria that has amylolytic ability. Identification of lactic acid bacteria can be detected by morphological include Gram stain, observation of cell shape, catalase test and testing of gas production from glucose. Thirty-six isolates were able to produce a clear zone on MRS agar medium supplemented with 0.2% CaCO3, and 10 of them were amylolytic. The identification results show that the 10 isolates were Gram-positive, short-form stem cells, catalase negative. Four isolates belong to the group of homofermentative LAB and six other isolates were heterofermentatif LAB. Suspected lactic acid bacteria were belonged to the genus Lactobacillus. Keywords : sago starch, isolation and identification, lactic acid bacteria, amylolytic ability, Lactobacillus